REKONSTRUKSI KURIKULUM BAHASA ARAB BERBASIS MODEL ROGERS: PENDEKATAN HUMANISTIK DALAM PEMBELAJARAN MAHĀRAH LUGHAWIYYAH - Anisah Firdausi; Maftukh Ghulam; Umi Hanifah (BEGIBUNG: Jurnal Penelitian Multidisiplin, 2026)
This article aims to reconstruct an Arabic language curriculum based on a humanistic approach by adopting Carl Rogers’ learning model. The main problem in Arabic language learning in Indonesia is the dominance of the structural-grammatical approach, which tends to neglect the affective aspects and individual needs of learners. This study employs a descriptive qualitative approach through a literature review, analyzing relevant literature on curriculum, humanistic theory, and language learning. The findings indicate that Rogers’ model, which emphasizes student-centered learning, freedom of learning, and authentic experiences, can serve as a foundation for reconstructing a more holistic Arabic language curriculum. This reconstruction includes the development of learning objectives, contextual materials, participatory strategies, and authentic assessment. The implementation of this model in mahārah lughawiyyah instruction has proven effective in enhancing students’ motivation, engagement, and communicative competence. This article recommends strengthening teacher training and reformulating the evaluation system to support the implementation of a humanistic curriculum